Análisis comparativo del cálculo de capacidad portante en base a geofísica y método covencional caso práctico Puente sobre el río Maicito - Naranjo Aguay, Héctor Xavier (2010)
The elaboration of this work begins with the need to know if the Method Geophysical and more concrete The Seismic Refraction Test gives us results acceptable and reliable in relation to the Conventional Methods applied in our country, to determine the calculation of the carrying capacity of the soil that is a fundamental tool for the construction of any civil work.